2013
DOI: 10.1149/2.025304jss
|View full text |Cite
|
Sign up to set email alerts
|

Wet Chemical Etching of InP for Cleaning Applications

Abstract: The wet chemical etching of InP and its native oxide has been studied in HCl and H 2 SO 4 solution to create oxide-free surfaces. The (100) InP surface is not etched in ≤2 M HCl and ≤6 M H 2 SO 4 . As the v etch <0.1 nm/min for these concentrations, the native oxide after OFOD treatment can be effectively removed without significantly etching the surface, as confirmed by contact angle measurements, ellipsometry and X-ray photoelectron spectroscopy. STM and AFM measurements showed that after OFOD treatment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 18 publications
2
38
0
Order By: Relevance
“…15 The measured indium cannot be explained by oxide removal only and is therefore attributed to the chemical etching of the semiconductor. By measuring the total amount of dissolved indium after immersion into the chemical solution, an approximate value for the etch rate could be determined.…”
Section: Resultsmentioning
confidence: 99%
“…15 The measured indium cannot be explained by oxide removal only and is therefore attributed to the chemical etching of the semiconductor. By measuring the total amount of dissolved indium after immersion into the chemical solution, an approximate value for the etch rate could be determined.…”
Section: Resultsmentioning
confidence: 99%
“…Highly anisotropic etching behavior, as evidenced by the formation of distinct etching pits, induces significant surface roughening. 34 In addition, formation of highly toxic AsH 3 is of important concern. Recently we demonstrated that these issues can be circumvented by using an oxidizing agent in the chemical solution.…”
Section: Chemical Etching In Hclmentioning
confidence: 99%
“…The striking difference in pit morphology for the two acids possibly originates from an anisotropy in V s . In earlier work, we demonstrated that the morphology of atomic terraces on InP (100) was different for H 2 SO 4 and HCl solution, supporting such a crystal orientation dependence [38,39].…”
Section: Etch Pit Formation In Bulk Inp (100)mentioning
confidence: 57%
“…Although the pit depth has been correlated to the energy of dislocations (e.g., edge versus screw) [35,36], the chemical properties of the Cottrell atmosphere may also have an impact [37]. Based on inductively coupled plasma mass spectrometry measurements, we estimate that V n is 2-3× larger than the bulk etch rate (V b ) of the (100) surface for both HBr and HCl [38]. The striking difference in pit morphology for the two acids possibly originates from an anisotropy in V s .…”
Section: Etch Pit Formation In Bulk Inp (100)mentioning
confidence: 93%
See 1 more Smart Citation